Analysis of the Use of HR Recruitment Systems on Employee Performance at Perumda Tirta Mangkaluku City of Palopo - Wardani, Reski; Bachri, Samsul; Makkasau, Suhandra (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to test how the HR recruitment system is carried out by Perumda Tirta Mangkaluku Palopo City in an effort to improve employee performance and also to find out what obstacles are faced by Perumda Mangkaluku City of Palopo in recruiting employees in an effort to improve the performance of its employees. The data analysis used in this study is using a quantitative method using simple linear regression analysis, conducting field studies such as (observations, interviews and documentation) which are carried out at the location of the research object The results of this research show that this recruitment system is very influential in improving employee performance at Perumda Tirta Mangkaluku City of Palopo because there is a science or a way of how to regulate the relationship between the roles of resources owned by individuals effectively and efficiently and can be used optimally so as to achieve the common goals of the company. So the process of hiring employees at Perumda Tirta Mangkaluku, Palopo City really fits the company's needs.